Comparison of the AVPU Scale and the Pediatric GCS in Prehospital Setting. (3rd July 2016) - Hoffmann, Florian; Schmalhofer, Michael; Lehner, Markus; Zimatschek, Sebastian; Grote, Veit; Reiter, Karl
Abstract: Objective: The pediatric Glasgow coma scale (pGCS) is a consciousness score that, although widely applied, requires skill to apply. The AVPU scale uses four simple categories (Alert; Verbal response; response to Pain; Unresponsive), but has not been studied in a large pediatric population. We compared the performance of the AVPU and pGCS scales in a large pediatric cohort in an acute, prehospital setting.Methods: In a six-month-long prospective cohort study, AVPU and pGCS scores were determined by emergency physicians in children less than 10 years of age at their first prehospital encounter.Results: We included 302 children (median age 2.3 years) with a broad spectrum of diagnoses. Data were complete for 287 children. AVPU and pGCS scores showed good a correlation in the extreme categories A and U (positive predictive values of 98% and 100%, respectively). Corresponding pGCS scores for each AVPU category were as follows: 11–15 for A; 5–15 for V; 4–12 for P; and 3–5 for U. The positive predictive value to detect patients with pGCS≥ 8 for AVPU category V was 100%.Conclusions: We demonstrated good correlation of simple and fast consciousness AVPU scoring to the standard pGCS in a large cohort of pediatric patients in a prehospital setting. The AVPU category "V" identifies patients with a pGCS of or exceeding 8 and, therefore, identifies children at low risk requiring more invasive procedures or intensive care treatment.Key words: Glasgow coma scale (GCS); Alert-verbal-pain-unresponsive-score; AVPU-score; consciousness assessment; children, pediatric emergency